Discussion - Of Mr. Barrows' Paper on the Use of High Percentages of Mesabi Iron-Ores in Coke Blast-Furnace Practice (see p. 140) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1905)
F. E. Bachman, Port Henry, N. T. (communication to the Secretary*):—In discussing Mr. o.o.Laudig's paper, the Action of Blast-Furnace Gases Upon Various Iron-Ores,' I took the ground that Mesabi-ore explosions were entirely mechanical; but more observation and later experience has caused me to